The Role of Twitter in Mobilizing Voter Turnout During Local Elections - Ayu Anggraini; Wikra Ardiansyah (Mahogany Journal De Social, 2024)
This paper aims to explore the role of Twitter in voter mobilization in local elections. The research is based on a mixed-methods design in which, quantitative and qualitative analysis is incorporated to give a broad picture. The quantitative aspect included content analysis of 3,000 tweets, related to the election, and a questionnaire of 500 respondents to quantify the influence of Twitter as a source of political information and the voting intention. The qualitative element involved in-depth interviews with politicians, campaign parties and voters and a case study of a mayoral race in a large city in Indonesia. The results show that influencer endorsements produced the best engagement even though they were not frequently used, whereas direct calls to action were also effective. According to the survey, the majority of the respondents used Twitter as their primary political source regularly and got motivated to vote because of their interactions online. The importance to real-time interaction, influencer support was noted in interviews as the way to improvement campaign visibility and voter turnout. The case study also showed that voter turnout had escalated greatly in cases where Twitter was highly used. On the whole, the results highlight the usefulness of Twitter as a strategic communication means of voter mobilization and the promotion of democracy.